Slip localization on the southern Alpine Fault, New Zealand. Issue 3 (14th June 2013) - Barth, N. C.; Boulton, C.; Carpenter, B. M.; Batt, G. E.; Toy, V. G.
Abstract [1] Results of a detailed field study of the southern onshore portion of New Zealand's Alpine Fault reveal that for 75 km along‐strike, dextral‐normal slip on this long‐lived structure is highly localized in phyllosilicate‐rich fault core gouges and along their contact with more competent rocks. At three localities (Martyr River, McKenzie Creek, and Hokuri Creek), we document complete cross sections through the fault. New 40Ar/39Ar dates on mylonites, combined with microstructural and mechanical data on phyllosilicate‐rich fault core gouges show that modern slip is localized onto a single, steeply dipping 1 to 12 m‐thick fault core composed of impermeable (k = 10−20 to 10−22 m2), frictionally weak (μs = 0.12–0.37), velocity‐strengthening, illite‐chlorite, and saponite‐chlorite‐lizardite fault gouges. Fault core materials are (1) comparable to those of other major weak‐cored faults (e.g., San Andreas Fault) and (2) most compatible with fault creep, despite paleoseismic evidence of quasiperiodic large magnitude earthquakes (Mw > 7) on this portion of the Alpine Fault. We conclude that frictional properties of gouges at the surface do not characterize the overall seismogenic behavior of the southern Alpine Fault.